A Map of Students’ Language Impoliteness: A Phenomenological Study - Kartini, Kartini; Anwar, Miftahulkhairah; Muliastuti, Liliana (JOLLT Journal of Languages and Language Teaching, 2024)
Recently, researchers have witnessed an alarming phenomenon related to the violation of language politeness among students. This study aims to describe the map of students’ language impoliteness in Indonesia. The research data is in the form of students’ speech. The focus of this research is unmannerly speech which is studied by phenomenological study by using Culpeper’s impoliteness strategy. The phenomenological steps taken are observation of the phenomenon of impoliteness, formulating problems, collecting data, analyzing data, and preparing reports. The research findings show that students use three politeness violation strategies, namely direct politeness violation, positive politeness violation, and negative politeness violation. The phenomenon found is the strategy of impoliteness by using four forms, namely delivering impolite speech directly, speech uttered based on consideration of the interlocutor, considering the location, and the situation of the conversation between the speaker and the interlocutor. This research can contribute to education, especially for teachers to always educate and guide students to speak politely. With a better understanding of the phenomenon of violations of students’ language politeness, it is hoped that appropriate preventive and intervention measures can be taken to minimize the forms of language impoliteness that can be carried out by a teacher or parent.